If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 9) + (2x + 8) + (2x) = (2x) + (2x) + (3x + 5) Reorder the terms: (9 + 2x) + (2x + 8) + (2x) = (2x) + (2x) + (3x + 5) Remove parenthesis around (9 + 2x) 9 + 2x + (2x + 8) + (2x) = (2x) + (2x) + (3x + 5) Reorder the terms: 9 + 2x + (8 + 2x) + (2x) = (2x) + (2x) + (3x + 5) Remove parenthesis around (8 + 2x) 9 + 2x + 8 + 2x + (2x) = (2x) + (2x) + (3x + 5) Reorder the terms: 9 + 8 + 2x + 2x + (2x) = (2x) + (2x) + (3x + 5) Combine like terms: 9 + 8 = 17 17 + 2x + 2x + (2x) = (2x) + (2x) + (3x + 5) Combine like terms: 2x + 2x = 4x 17 + 4x + (2x) = (2x) + (2x) + (3x + 5) Combine like terms: 4x + (2x) = 6x 17 + 6x = (2x) + (2x) + (3x + 5) Reorder the terms: 17 + 6x = (2x) + (2x) + (5 + 3x) Remove parenthesis around (5 + 3x) 17 + 6x = (2x) + (2x) + 5 + 3x Reorder the terms: 17 + 6x = 5 + (2x) + (2x) + 3x Combine like terms: (2x) + (2x) = 4x 17 + 6x = 5 + 4x + 3x Combine like terms: 4x + 3x = 7x 17 + 6x = 5 + 7x Solving 17 + 6x = 5 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 17 + 6x + -7x = 5 + 7x + -7x Combine like terms: 6x + -7x = -1x 17 + -1x = 5 + 7x + -7x Combine like terms: 7x + -7x = 0 17 + -1x = 5 + 0 17 + -1x = 5 Add '-17' to each side of the equation. 17 + -17 + -1x = 5 + -17 Combine like terms: 17 + -17 = 0 0 + -1x = 5 + -17 -1x = 5 + -17 Combine like terms: 5 + -17 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| y=Ax^3+Bx^2+Cx | | 3(r-4)=-9 | | 64m^2+144m+81=0 | | 6(x+9)=-26-4x | | 8+10x= | | 21-a+4a=6 | | 2+6(7-x)=20 | | [4(x+2)]+9=15 | | (-12x-3)(12x^2-11x+3)= | | 3a^3-4a=-4a^2 | | 6x+5=6x+7 | | (.36x^2)-9x-7000=0 | | 2x^2+23x-8.1=0 | | 18=7(b-1)+4(1-7b) | | [2(x-3)]=10 | | 140=11x+9 | | 4(c+7)=7+c | | -5x+4y=31 | | 4ln+8l=56 | | -4[s+9]=-24 | | 5a-5=4a+2 | | 5(y-1)=3y+5 | | 81x^2+18x+6=0 | | 2[2r+4]=-16 | | [3(x-1)]=15 | | r^2-10r+2=0 | | 8-3.5x=2808 | | 0.9x-0.3(4-x)=6.6 | | 2x-11=y | | 6(3+x)=5(x-6) | | 4a=2(a+2)-12 | | y-3=2(-1+1) |